(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: cleft lip and palate (CLP) is a type of a congenital cranio-facial development malformation. The Previous studies show a widely prevalence of this malformation Also show a lack of knowledge and awareness toward the parents, that results in a lot of complications in speech, nutrition, and hearing and even a psychological issue. Objective: This observational study aimed to assess the awareness and attitudes of parents towards cleft lip and palate in subsets populations in Saudi Arabia. Methods: In this study, a cross-sectional analytical study was conducted among the parents to investigate the awareness level and attitudes of parents towards cleft lip and palate (CLP) in subsets populations in Saudi Arabia. Before the beginning of the study, ethical approval for this study was obtained from the institutional review board (IRB). Also, the questionnaire was distributed through social media platforms such as Twitter, Telegram, and WhatsApp. The English language was used in both the text messages and the questionnaire. Participants were informed about the aim of the study as well as their participation in the questionnaire survey is voluntary and anonymous. The items of the questionnaire study are performed and sent to parents generally and parents accompanying infants with cleft lip and palate in Saudi Arabia. Results: the total sample size were 461 participants. As regards awareness and attitude score revealed that 59% had neutral attitude, 21% had negative attitude and only 20% had positive attitude. Moreover, there was no significant association between participants’ attitude scores with their sociodemographic characters (P>0.05). Conclusion: The findings revealed a significant proportion displaying neutral or negative attitudes towards the condition. While there was no significant association between attitude scores and sociodemographic characteristics, it is crucial to continue educating and raising awareness among parents to improve their understanding and support for individuals with cleft lip and palate.